Europejski Trybunał Praw Człowieka – przegląd orzecznictwa (styczeń–marzec 2022 r.) - Nowicki, Marek Antoni (Palestra, 2024)
The review of the case law presents the most significant views expressed in judgments and decisions issued by the European Court of Human Rights between January and March 2022, concerning the right to life, prohibition of torture, right to a tribunal established by law, right to respect for private and family life, freedom of expression, freedom of assembly and association, right to free elections. The review is followed by a comprehensive summary of the judgment of the European Court of Human Rights (Section I) in the Advance Pharma sp. z o.o. v. Poland case concerning manifest breaches, following legislative reform, in appointment to Supreme Court’s Civil Chamber of judges who examined applicant company’s civil appeal.